Influence of Vitamin D and Parathyroid Hormone on Bone and Metabolic Risk in Women with Previous Gestational Diabetes - Serra, M. C.; Ryan, A. S. (Hormone and Metabolic Research, 2016)
The purpose of this study was to compare plasma 25-hydroxyvitamin D [25(OH)D] and parathyroid hormone (PTH), VO2max, bone (by DXA), and metabolic outcomes across age and race-matched postmenopausal women (54±1 years; mean±SEM): 1) with previous gestational diabetes (GDM) (32±1 kg/m2; n=17), 2) without previous GDM, but with a similar BMI to GDM (32±1 kg/m2; n=17), and 3) without previous GDM, but with a higher BMI than GDM (36±1 kg/m2; n=17; p<0.01). The prevalence of 25(OH)D insufficiency and deficiency was high (~80%), but not different across groups, while PTH tended to be ~30% lower in women with a history of GDM (p=0.09). Women with a history of GDM had lower HDL cholesterol and higher diastolic blood pressure and fasting and 2-h glucose levels (by oral glucose tolerance test) (vs. groups 2 and 3; p<0.05). Bone mineral density (BMD) tended to be slightly higher in women with prior GDM than the BMI matched women with no prior GDM (p=0.09). Overall, higher PTH was associated with lower femoral neck (r=− 0.33) and (r=− 0.38) (p <0.05), while lower 25(OH)D was associated with lower VO2max (r=0.25, p=0.05) and higher fasting glucose (r=− 0.14) and insulin (r=− 0.29 (p <0.05). We observed that the poor metabolic profiles of postmenopausal women with a history of GDM are independent of 25(OH)D and PTH. However, due to associations between 25(OH)D and PTH with bone and metabolic outcomes, maintaining recommended 25(OH)D and PTH concentrations is important regardless of a previous history of GDM.
Keywords: gestational diabetes mellitus; vitamin D; parathyroid hormone; metabolism; bone mineral density